PENYEBARAN KONTEN PORNOGRAFI MELALUI TELEGRAM BERBASIS KODE (STUDI FENOMENOLOGI PADA CHANNEL KODE NUKLIR) - Nilam Putri Kirana; Vannyora Okditazeini (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
The dissemination of pornographic content through Telegram, based on codes,makes it easier for users to enjoy such content without fear of detection by third parties.This research is motivated by the numerous crimes and sexual violence incidents attributedto excessive pornography consumption. The aim of this study is to examine how this contentis generated, distributed, consumed, and to understand the significance of using nuclearcodes among Otaku. This qualitative descriptive research utilizes a phenomenological studymethod. The findings of this research indicate that nuclear codes are not generatedmanually but automatically from content provider servers. The distribution of nuclear codesfollows a cyclic pattern, while the consumption of nuclear codes aligns with the Diffusion ofInnovations theory stages: awareness, evaluation, trial, and adoption. The meaningsattributed to their use include personal satisfaction, fetish, and incognito browsing.Interestingly, the largest consumption of these codes is associated with yaoi/boys love genrecontent.